Pengaruh Pelayanan dan Citra Merek terhadap Kepuasan Pengguna Gojek di Jakarta Selatan - Ayu Rismawati; Husnayetti Husnayetti (ITB Ahmad Dahlan Jakarta, 2021)
The purpose of this study is to examine the effect of service and brand image.And analyze the magnitude of the impact of service quality and brand image on Gojek users' satisfaction in Jakarta. And to find out and analyze the most dominant factors that influence customer satisfaction. This research was conducted on Gojek user customers. The research design used is quantitative associative to determine the relationship of three variables, variable x1 (service), x2 (brand image), and y variable (customer satisfaction). The method used is a simple random sampling that is sampling from a random population without regard to the existing strata in that population. The measurement scale of the research instrument uses a Likert scale. The analytical method used in this research is multiple linear regression analysis, y = 1.327 + 0.443 x1 + 0.498 x2, for the coefficient of determination of 0.594 this shows that the contribution of service quality and brand image to customer satisfaction Gojek users in Jakarta amounted to 59.4 % and 40.6% influenced by other factors or variables. For the results of the t-test